Characteristic patients with oral mucositis receiving 5-FU chemotherapy at Hasan Sadikin Hospital Bandung - Fatimah, Syarifah; Sufiawati, Irna; Wijaya, Indra (Padjadjaran Journal of Dentistry, 2016)
Introduction: Oral mucositis is an inflammatory reaction of oral mucous membrane that often appears in cancer patients due to the chemotherapeutic agents, such as 5-fluorouracil (5-FU). The aim of this study was to describe the characteristic patients who receive 5-FU and had oral mucositis. Methods: This study was conducted on 41 patients with cancer receiving 5-FU chemotherapy at Dr Hasan Sadikin Hospital Bandung. The data was retrieved through interviews to find out patientâs characteristic; nutritional status examination by using body mass index measurement; and oral examination. Severity level was determined by using National Cancer Instituteâs Common Toxicity Criteria scale, and the level of pain was measured by Numeric Pain Intensity Rating scale. Results: This research have shown 60,98% patient with cancer had received 5-FU chemotherapy treatment, and 44% with poor nutritional status (underweight). Oral mucositis was only found at non-keratinised mucous. The finding of this study was patients that receiving 5-FU chemotherapy treatment diagnosed with oral mucositis was on the 1st stadium (52%) and the 2nd stadium (44%) with the level of pain was on the mild level (48%) and moderate level (32%).Conclusion: Oral mucositis was found on patients with cancer that received 5-FU chemotherapy with a variety of characteristics, nutritional statuses, locations, levels of severity and pain.